Physical exercise, health, and disease treatment: The role of macrophages - Callegari, Irineu O. M.; Rocha, Guilherme Z.; Oliveira, Alexandre G. (Frontiers in Physiology, 2023)
Subclinical inflammation is linked to comorbidities and risk factors, consolidating the diagnosis of chronic non-communicable diseases, such as insulin resistance, atherosclerosis, hepatic steatosis, and some types of cancer. In this context, the role of macrophages is highlighted as a marker of inflammation as well as for the high power of plasticity of these cells. Macrophages can be activated in a wide range between classical or proinflammatory, named M1, and alternative or anti-inflammatory, also known as M2 polarization. All nuances between M1 and M2 macrophages orchestrate the immune response by secreting different sets of chemokines, while M1 cells promote Th1 response, the M2 macrophages recruit Th2 and Tregs lymphocytes. In turn, physical exercise has been a faithful tool in combating the proinflammatory phenotype of macrophages. This review proposes to investigate the cellular and molecular mechanisms in which physical exercise can help control inflammation and infiltration of macrophages within the non-communicable diseases (NCD) scope. During obesity progress, proinflammatory macrophages predominate in adipose tissue inflammation, which reduces insulin sensitivity until the development of type 2 diabetes, progression of atherosclerosis, and diagnosis of non-alcoholic fatty liver disease. In this case, physical activity restores the balance between the proinflammatory/anti-inflammatory macrophage ratio, reducing the level of meta-inflammation. In the case of cancer, the tumor microenvironment is compatible with a high level of hypoxia, which contributes to the advancement of the disease. However, exercise increases the level of oxygen supply, favoring macrophage polarization in favor of disease regression.